Transcriptional Innate Immune Response of the Developing Chicken Embryo to Newcastle Disease Virus Infection - Schilling, Megan A.; Katani, Robab; Memari, Sahar; Cavanaugh, Meredith; Buza, Joram; Radzio-Basu, Jessica; Mpenda, Fulgence N.; Deist, Melissa S.; Lamont, Susan J.; Kapur, Vivek (Frontiers in Genetics, 2018)
Traditional approaches to assess the immune response of chickens to infection are through animal trials, which are expensive, require enhanced biosecurity, compromise welfare, and are frequently influenced by confounding variables. Since the chicken embryo becomes immunocompetent prior to hatch, we here characterized the transcriptional response of selected innate immune genes to Newcastle Disease virus (NDV) infection in chicken embryos at days 10, 14, and 18 of embryonic development. The results suggest that the innate immune response 72 hours after challenge of 18-day chicken embryo is both consistent and robust. The expression of CCL5, Mx1, and TLR3 in lung tissues of NDV challenged chicken embryos from the outbred Kuroiler and Tanzanian local ecotype lines showed that their expression was several orders of magnitude higher in the Kuroiler than in the local ecotypes. Next, the expression patterns of three additional innate immunity related genes, IL-8, IRF-1, and STAT1, were examined in the highly congenic Fayoumi (M5.1 and M15.2) and Leghorn (Ghs6 and Ghs13) sublines that differ only at the microchromosome bearing the major histocompatibility locus. The results show that the Ghs13 Leghorn subline had a consistently higher expression of all genes except IL-8 and expression seemed to be subline-dependent rather than breed-dependent, suggesting that the innate response of chicken embryo to NDV infection may be genetically controlled by MHC-locus. Taken together, the results suggest that the chicken embryo may represent a promising model to studying the patterns and sources of variation of the avian innate immune response to infection with NDV and related pathogens.